Conflict, Carnage, and Cats: Toward a Comic Cú Chulainn in Martin McDonagh's "The Lieutenant of Inishmore" - Knox, A. J. (Comparative drama, 2013)
There are certain thematic, ideological, and figural connections between Cú Chulainn, the epic hero of the "Táin Bó Cúailnge" of Ireland's mythological Ulster Cycle, and Padraic from Martin McDonagh's "The Lieutenant of Inishmore." Knox utilizes the mythology of Cú Chulainn as a lens through which to view McDonagh's contemporary exploration of the Irish "hero" as it pertains to both theatrical and cultural spheres. Through a comparative study of the two texts, he examines the ways in which "The Lieutenant of Inishmore" satirizes ideologies permeating the sectarian conflict in Ireland during the latter half of the 20th century. Knox analyzes McDonagh's comic subversion of Cú Chulainn's status as a symbol for Irish nationalism, leading to the development and construction of a postmodern comic hero for a divided Ireland.